Valorization of plastic waste in concrete for sustainable development - Bentegri Houcine; Rabehi Mohamed; Kherfane Samir; Boukansous Sarra (The Journal of Engineering and Exact Sciences)
Environmental preservation issues are hot topics, as they have come to the fore in recent years due to climate change and the significant pollution that is occurring in the environment especially that related to plastic waste, because the problem of their disposal has become a problem from which governments suffer. We have therefore decided in this study to recycle and recover plastic and are going to study the possibility of replacing the aggregates present in the concrete with plastic granules and to study the physical and mechanical properties of this type of concrete, where the aggregates (sand + gravel) in the concrete will be replaced by plastic aggregates (PET) in variable proportions (0%, 5%, 10%, 15%, 20%, 25%, 30%) in relation to its volume. The results obtained have shown good results, especially in terms of reducing the weight of the concrete and in terms of sound insulation, The aggregates (PET) reduce the compressive strength but not significantly, in the end we can say This type of concrete opens up new horizons and gives a new vision of concrete that respects the environment and sustainable development.